A COMPARISON OF THREE NUMERICAL METHODS OF SOLUTIONS OF EQUATIONS DESCRIBING UNSTEADY GAS FLOW AT PIPE BOUNDARIES IN RECIPROCATING COMPRESSOR SYSTEMS - Mkumbwa, M. H. (Tanzania Journal of Engineering and Technology, 2018)
Abstract